2016
DOI: 10.18769/ijasos.10659
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Based on Gender in Iranian Food Culture

Abstract: The purpose of this study is to reveal how gender differentiation in the food preparation and consumption behaviors crystallizes in Iran. To this end, observations were made in Tehran, the capital city of Iran, for a period of one month in 2014. Apart from the observations, in order to be able to determine gender differentiations and gender roles in regard to food preparation and consumption, interviews were also held with ten people from different jobs, genders and ages using a semi-structured interview form.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(10 reference statements)
0
1
0
1
Order By: Relevance
“…According to Iran’s Civil Code, men are considered as the head of the household, the breadwinner of the family, and the guardian of women; they are responsible for providing the necessities of women’s lives such as food, shelter, and health care [25]. It has been shown that in Iranian families, men usually do the shopping for food and decide what dish should be cooked [26]. Also, the sex difference may be due to some major limitations and challenges married women face in Iran; for instance, a husband often forbids his wife from joining a sports team, cycling, and exercising outdoors [27].…”
Section: Discussionmentioning
confidence: 99%
“…According to Iran’s Civil Code, men are considered as the head of the household, the breadwinner of the family, and the guardian of women; they are responsible for providing the necessities of women’s lives such as food, shelter, and health care [25]. It has been shown that in Iranian families, men usually do the shopping for food and decide what dish should be cooked [26]. Also, the sex difference may be due to some major limitations and challenges married women face in Iran; for instance, a husband often forbids his wife from joining a sports team, cycling, and exercising outdoors [27].…”
Section: Discussionmentioning
confidence: 99%
“…Yapılan birçok araştırma erken yaşlarda sosyal ve duygusal gelişime yönelik hazırlanan eğitim programları sonucunda, çocukların gelişimlerinde olumlu sonuçlar elde edildiğini gösterir (Avcıoğlu, 2003;Domitrovich, Cortes & Greenberg, 2007;Durmuşoğlu Saltalı, 2010;Ekinci Vural, 2006;Izard, Fine, Schultz, Mostow, Ackerman & Youngstrom, 2001;Yukay, 2006;). Erken müdahale ile sosyal/duygusal gelişimin yörüngesinin değiştirilebilir ve önemli oranda geliştirilebilir olduğu görülmektedir (Sprague & Walker, 2000).…”
Section: Introductionunclassified